Aging and Urban House Prices. - Lerbs, Oliver; Hiller, Norbert (My University, 2015)
This paper investigates the long-run relationship between the size and age structure of a city s resident population and the price of local housing. For estimation purposes, we combine city-level demographic information with housing price data for 87 cities in Germany over 1995-2012. Employing a panel error correction framework that accounts for the evolution of city in-come and housing financing costs, we find that real urban house prices per-form stronger in cities that age less rapidly. A combination of the empirical estimates with current population projections suggests that population aging will exert considerable downward pressure on urban house prices in upcoming years.
Keywords: Wohnungswesen; Wohngebäude; Eigentumswohnung; Kaufpreis; Preisentwicklung; Stadtgröße; Bevölkerungsstruktur; Altersstruktur